The Influence of Financial Distress, Audit Specialization, Opinion Shopping, and Prior Opinion on Going Concern Audit Opinion - Hidayati, Afifah Noor; Wulandari, Putu Prima (Telaah Ilmiah Akuntansi dan Perpajakan, 2026)
This quantitative study aims to determine the influence of financial distress, audit specialization, opinion shopping, and prior opinion on going concern audit opinion. Using a purposive sampling method, 85 manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period were selected as the sample. The results of logistic regression analysis show that only opinion shopping affects the likelihood of receiving a going concern audit opinion. In contrast, financial distress, audit specialization, and prior opinion have no significant effect. This study supports agency theory, which posits that auditors act as independent parties in bridging the information asymmetry between management (the agent) and company owners (the principal).